Mental Health of Staff at Correctional Facilities in the United States During the COVID-19 Pandemic - Burhanullah, M. Haroon; Rollings-Mazza, Pamela; Galecki, Jeffrey; Van Wert, Michael; Weber, Thomas; Malik, Mansoor (Frontiers in Psychiatry, 2022)
Background: Although United States (US) correctional workers (correctional officers and health care workers at correctional institutions) have experienced unprecedented stress during the COVID-19 pandemic, to date, there is no systematic data on the mental health impact of COVID-19 on correctional workers. Objective: To determine the mental health burden of the COVID-19 pandemic on correctional workers and to explore the relationship between workers’ mental health, social demographics and environmental/work factors. In particular, the study sought to examine if occupational role (correctional officers vs. health care workers) or gender were associated with mental health status. Methods: This cross-sectional survey was conducted in seventy-eight correctional sites in Pennsylvania, Maryland, West Virginia and New York from November 1 to December 1, 2020. There were 589 participants, including 103 correctional officers and 486 health care workers employed at the correctional facilities. Measurements included the Patient Health Questionnaire-9, Generalized Anxiety Disorder-7, Adult PROMIS Short Form v.1.0—Sleep Disturbance, Impact of Event Scale-Revised, Maslach Burnout Inventory 2-item, and Connor-Davidson Resilience Scale 2-item. Results: Approximately 45% reported depressive symptoms, 50% reported anxiety symptoms, 46% reported symptoms of burnout, and 52% reported post-traumatic symptoms. Health care workers had significantly higher depression, anxiety, and sleep disturbance scores than did correctional officers, while correctional officers had significantly higher burnout scores. Female correctional workers scored significantly higher on anxiety than their male counterparts. Increased workload, workplace conflict, younger age of employees, trust in institutional isolation practices, and lower work position were associated with increased burnout. Despite their high mental health burden, correctional workers showed high resilience (60%). Conclusion: We found a high level of psychological symptoms among health care workers in correctional settings, and this population may experience unique challenges, risks and protective factors relative to other health care workers outside of correctional settings. Understanding these factors is essential for developing effective interventions for correctional workers (correctional officers and health care staff at correctional institutions)